Circulating adipokines involved in atrial fibrillation and obesity: a comprehensive scoping review. (19th May 2022) - Meulendijks, E; Krul, SPJ; Baalman, SW; Wesselink, R; Al-Shama, RF; Ernault, CCE; Limpens, J; Kawasaki, M; Vries, TAC; Neefs, J; De Groot, JR
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Received research grants (through institution) from Atricure Inc, Bayer, Boston Scientific, Daiichi Sankyo, Johnson&Johnson, Medtronic Received honoraria/speaker/consultancy fees from Abbott, AtriaN Medical, Atricure Inc, Bayer, Biotronik, CVOI, Daiichi Sankyo, IPP Med, Itreas, Medtronic, Novartis, Servier Background: Obesity increases the risk of atrial fibrillation (AF). Obesity may induce or facilitate AF via adipokines, proteins secreted by metabolically active adipose tissue (AT). These adipokines potentially affect atrial electrical and structural remodeling. Therefore, adipokines could be targets in the management of AF. Purpose: Here, we aim to give a comprehensive overview of circulating adipokines, defined as proteins expressed in adipose tissue, associated with pre-existing or new-onset AF as well as their relationship with obesity. Methods: A systematic, explorative primary search was conducted for studies reporting corrected odds and hazard ratios (ORs, HRs) of adipokines in pre-existing AF, and in new-onset AF. Adipokine-ratios were aggregated into processes involved in AF substrate formation. Next, a secondary search was performed to investigate the association between the identified adipokines and obesity. Results: Sixty-three distinct adipokines were identified, 49 in pre-existing AF (78 corrected ORs), and 34 in new-onset AF (76 corrected HRs). These included adipocyte specific adipokines as FABP4, and adipokines expressed by both adipocytes and other cells residing in the fat, as interleukin 6 (IL-6). The majority of identified adipokines were involved in inflammatory and fibrotic pathways. Most inflammatory adipokines were significantly increased in pre-existing AF (20/33ORs), and half in new-onset AF (14/28 HRs). Approximately half of the fibrotic adipokines were increased in pre-existing AF (12/25 ORs) and in new-onset AF (8/17 HRs). The secondary search showed that in obesity, most (33) of the 63 identified adipokines in AF were increased, including IL-6. Twenty-four were not affected, and 6 were decreased. Candidate pro-arrhythmogenic inflammatory, and fibrotic adipokines increased in both AF and obesity are shown in the figure. Conclusion: Most pro-inflammatory and fibrotic circulating adipokines, associated with AF pathology, were either increased or showed a strong trend towards increased levels in both pre-existing and new-onset AF, as well as in obesity. Our review provides insight into the effect of obesity on circulating adipokines involved in AF substrate formation.